Antisecretory treatment efficacy by proton pump inhibitors at gastroduodenal ulcer bleedings - M. A. Evseyev; I. M. Klishin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To assess clinical efficacy of antisecretory drugs at gastroduodenal ulcer bleedings.Original positions. Parenteral forms of Н2-blockers as conservative hemostasis components showed efficacy which statistically does not differ from that of placebo. Metaanalysis of 18 studies revealed, that continuous intravenous infusion of omeprazole significantly reduces frequency of recurrent hemorrhage. Parenteral injection of esomeprazole after endoscopic hemostasis provides highly effective decrease in frequency of recurrent ulcer bleeding in the first 72 hs of hospital stay, as well as for the next 7 and 30 days.Conclusion. Prolonged intravenous injection of esomeprazole with subsequent intake of the drug per os is proved for application in clinical practice for patients with bleeding stomach and duodenum ulcers after endoscopical verification of hemostasis.